2018
DOI: 10.1136/bmjopen-2018-021874
|View full text |Cite
|
Sign up to set email alerts
|

Impact of workplace incivility in hospitals on the work ability, career expectations and job performance of Chinese nurses: a cross-sectional survey

Abstract: ObjectivesThe objectives of this study were to investigate new nurses’ experiences of workplace incivility; verify the mediating role of work ability in the relationship between workplace incivility and job performance and examine the moderating role of career expectations in the relationship between workplace incivility and job performance.DesignThis cross-sectional survey was conducted in China in May 2016.SettingsThe research settings included 54 cities across 29 provinces of China.ParticipantsOf the 903 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
(40 reference statements)
2
34
0
3
Order By: Relevance
“…Those who experience harmful incidents have a higher chance of developing poor well‐being and self‐care, which might weaken their work performance, than those who do not. In the analysis of Zhang et al (), incivility unfavourably sets back the cognitions and emotions of nurses and significantly reduces their self‐confidence towards patient care. Poor self‐confidence towards care and responsibility could lead to low QNC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who experience harmful incidents have a higher chance of developing poor well‐being and self‐care, which might weaken their work performance, than those who do not. In the analysis of Zhang et al (), incivility unfavourably sets back the cognitions and emotions of nurses and significantly reduces their self‐confidence towards patient care. Poor self‐confidence towards care and responsibility could lead to low QNC.…”
Section: Discussionmentioning
confidence: 99%
“…Poor self‐confidence towards care and responsibility could lead to low QNC. A harmonious compassionate milieu can increase in providing humanistic (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Bambi et al (2018) indicated that nurse education level is not a related factor of lateral violence and uncivil behaviors among nurses in clinical settings. However, Zhang et al (2018) reported that differences in education level in workplace incivility scores were statistically significant. In addition, they indicate that nurses with higher education degrees find there is a gulf between the theoretical and the actual workplace, and struggle when faced with the challenge to adapt to the new environment and organizational culture, with poor performance leading to admonition and workplace incivility.…”
Section: Discussionmentioning
confidence: 93%
“…Dismissive actions can be verbal or nonverbal. Eye‐rolling and ignoring an individual are two actions described in the literature. Dismissive actions were found to undervalue the individual and his or her contributions to the nursing profession …”
Section: Resultsmentioning
confidence: 99%